Conocimiento de las mujeres, educación y desarrollo. Modelo educativo desde una investigación-acción participativa con un grupo de mujeres Mayas en Guatemala - Galeotti, Glenda (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
This article starts from a reflection on the relationship between women's knowledge, education and practices of development that moves from an action research with a group of Mayan women of Guatemala. The study shows an educational model able to promote social inclusion of women, starting from valorization of their know-how on nature, with also positive effects on the well-being of the whole community. The article finally outlines the possible contribution of adult education to international cooperation projects also in terms of governance of cultural and gender differences.